MODERN VIEW ON THE IMMUNE MECHANISMS OF OSTEOARTHRITIS FORMATION - Tohirova N.S; Ganieva Sh.Sh (Scholar Express Journals, 2022)
Osteoarthritis is both a general medical and socio-economic problem, characterized by the development of functional disorders in the joints, loss of working capacity, disability of patients and, thereby, a decrease in their quality of life, significant financial costs. The review article presented by the authors systematizes modern research by foreign authors, including metabolic shifts, inflammatory processes, immune disorders.
Keywords: Osteoarthritis; immune mechanisms; pathogenesis; severe syndrome